Factors affecting attitudes toward e-shopping in the United Arab Emirates - Abdallah M. Elamin; Liaqat Ali; Ahmed Zain Elabdin Ahmed; Hazem Aldabbas (Cogent Business & Management)
This study examines shoppers’ attitudes toward online shopping in the United Arab Emirates (UAE). The researchers investigate the effects of perceived benefits, trust, electronic word of mouth (e-WOM) and perceived website quality as antecedents shaping buyer attitudes. The researchers also investigated the effect of e-WOM and perceived website quality on the development of trust in shopping websites. A sample of 236 online shoppers was included in the survey. Correlation and hierarchical regression analyses were used to test the hypothesized relationships. The findings reveal that perceived benefits, e-WOM, and trust are significant determinants of a positive attitude toward e-shopping. Perceived website quality and e-WOM are direct predictors of trust. This study deepens the understanding of online shoppers’ attitudes toward e-shopping and their perceptions of its benefits, e-WOM, website quality, and trust. Importantly, this study outlines and discusses practical implications for e-marketers in the UAE.